Anatomical, functional, and blood-born predictors of severity of brachycephalic obstructive airway syndrome severity in French Bulldogs - Schmid, Claudia; Steiner, Aline R.; Spielhofer, Léonie; Galfetti, Meltem; Rentsch, Nikki; Bogdanov, Nikolay; Vogel, Johannes; Hofmann-Lehmann, Regina; Hartnack, Sonja; Astakhov, Georgy; Furrer, Reinhard; Bogdanova, Anna; et al. (Frontiers in Veterinary Science, 2025)
Brachycephalic breeds suffer from respiratory distress known as brachycephalic obstructive airway syndrome (BOAS) and the multiple comorbidities associated with it. Targeted breeding toward a more BOAS-free phenotype requires accurate and least invasive detection of BOAS severity grades that are accessible and accepted by the breeders and kennel clubs. This study aimed to compare the-outcome of morphometric anatomical examination with functional tests such as exercise tests and plethysmography for the detection of BOAS severity in a group of 84 French Bulldogs. In addition, we investigated the possibility of assessing the severity of BOAS using blood parameters that were found to vary between the brachycephalic and non-brachycephalic dogs in our previous study. We found the results of the trotting test to be most reliable compared to the outcome of respiratory performance assessment using plethysmography. Of all the candidate blood parameters tested, carboxyhemoglobin and oxyhemoglobin levels were the most predictive as on-side but not self-standing indicators of BOAS severity grade. Aggravation of BOAS manifestation was associated with mild stress erythropoiesis and oxidative stress. Based on our findings, we suggest continuing to use the trotting test as the method of choice for the selection of breeding dogs; in questionable cases, a temperature increase of more than 0.4°C indicates at least grade 2. Furthermore, co-oximetry could be used as an additional test to enable assignment to one of the two BOAS grades in dispute. Among the limitations of this study are the focus on one breed and the low number of animals with severe clinical signs of BOAS in the study cohort.